Storage stability of anti-Salmonella Typhimurium immunoglobulin Y in immunized quail eggs stored at 4°C - ESMAILNEJAD, ATEFEH; HACHESOO, BAHMAN ABDI; NASAB, ELHAMSADAT HOSSEINI; SHAKOORI, MARYAM (The Indian Journal of Animal Sciences, 2020)
Chicken egg yolk antibodies (IgYs) are extensively used for immunotherapy and immunodiagnostic purposes. Oral immunotherapy with specific IgYs is established as an efficient alternative to traditional antibiotic therapy in human and animals. Storing immunized eggs in refrigerator for a period of time could provide an inexpensive and convenient source of large volumes of specific antibodies. This study investigated the storage stability of anti- Salmonella Typhimurium IgYs in immunized quail egg yolks at 4°C over a period of more than 6 months. Salmonella spp.-free female Japanese quails (Coturnix coturnix japonica) were intramuscularly immunized whit Salmonella Typhimurium whole bacterial suspension (1.0×109 CFU/ml) emulsified with Freund adjuvants. During a period of 10 days after final immunization, eggs from each group were collected, randomized and stored at 4°C over a period of 200 days. Egg yolk IgY titer and specificity were determined using ELISA technique. S. Typhimurium specific IgY antibodies were detected in immunized quails and were significantly higher than the control group which confirmed the immunization procedure. Eggs from immunized quails can be collected and stored in 4°C refrigerator over a period of 2 months without any concern about the antibody degradation. After 80 days of storage at 4°C, although lower antibody titer was obtained in comparison to the first of study, anti-S. Typhimurium IgY level remained stable up to the 6 months without more significant declining. This trend will provide economical sources of polyclonal antibodies through reducing the number of immunized animals, management expenses and housing costs.